Diagnostic value of CD206+CD14+ macrophages in diagnosis of lung cancer originated malignant pleural effusion - Pei, Xue-Bin; Wu, Xiu-Zhi; Yi, Feng-Shuang; Zhai, Kan; Shi, Huan-Zhong (Journal of Thoracic Disease, 2019)
Background: Pleural effusions are common complications of various diseases. Patients with malignant pleural effusion (MPE) usually face poor prognosis and short life expectancy. Discriminating between MPE and benign pleural effusion remains to be difficult. The aim of our current study was to evaluate whether CD206+CD14+ macrophages could be a diagnostic biomarker for MPE. Methods: The percentages of CD14+, CD86+CD14+ and CD206+CD14+ macrophages in pleural effusions were determined by flow cytometry in 34 patients with MPE and 26 with benign pleural effusion, and their diagnostic performances were evaluated by receiver operating characteristic (ROC) curves. Results: The percentages of CD14+, CD86+CD14+ and CD206+CD14+ macrophages were remarkably higher in MPE than in benign pleural effusion (all P